Epidemiological Scenario of American Trypanosomiasis and Its Socioeconomic and Environmental Relations, Pará, Eastern Brazilian Amazon - Claudia do Socorro Carvalho Miranda; Bruna Costa de Souza; Tainara Carvalho Garcia Miranda Filgueiras; João Simão de Melo Neto; Amanda Sophia Carvalho Miranda da Silva; Hilton Pereira da Silva; Marcos Valério Santos da Silva; Frederico Itã Mateus Carvalho Oliveira Miranda; Edilene do Socorro Nascimento Falcão Sarges; Sérgio Luiz Althoff; Selma Kazumi da Trindade Noguchi; Nelson Veiga Gonçalves (Tropical Medicine and Infectious Disease)
Chagas disease is a serious public health problem worldwide. In Brazil, the state of Pará has the largest number of reported cases. This article analyzes the spatial distribution of this disease and its relationship with socioeconomic, environmental, and public policy health variables in three mesoregions in the Pará state from 2013 to 2022. This ecological study used secondary data obtained from official Brazilian agencies. Spatial analysis was carried out using the flow, kernel, and bivariate global Moran techniques expressed in thematic maps. A total of 3664 cases of the disease were confirmed, with the highest number of cases being reported in the northeast of Pará. A seasonal pattern of the disease, an epidemiological profile similar to other diseases in the Amazon region, and the spatial dependence between the disease prevalence and socioeconomic indicators were observed. The most intense movement of patients for treatment was to the Belém metropolitan mesoregion, which has the majority of the health services and professionals. The disease showed an inhomogeneous pattern of cases in terms of the spatial distribution, with a direct relationship between areas with a higher number of cases and those with human clusters. The socioenvironmental origins of the disease transcend mesoregion boundaries and stem from the historically unsustainable development model in the Amazon.